3d-transition metal catalyzed C–H to C–N bond formation: An update. (5th November 2021) - Singh, Ritesh; Sathish, Elagandhula; Gupta, Ashis K.; Goyal, Sophiya
Abstract: Direct C–H bond amination is an emerging area of research among synthetic community owing to prevalence of N-bearing scaffolds in various fields of importance to humankind. In this direction, use of 3d transition metals (Cu, Co, Ni and Fe) have recently emerged as promising class of catalytic promoters for C–H to C–N bond formation through different mechanistic manifolds in order to make the transformation more sustainable and industrially oriented. Herein, we provide an update on 3d-transition metal mediated C–H bond amination reactions showcasing the recent developments in this area, thus clearly outlining the scope and limitations of the developed methods and illustrating the focus area to be addressed in the near future. Graphical abstract: Image 1